2020
DOI: 10.4045/tidsskr.20.0239
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinstormer ved covid-19?

Abstract: Kari Tveito er lege, ph.d. og medisinsk redaktør i Tidsskriftet. Forfatteren har fylt ut ICMJE-skjemaet og oppgir ingen interessekonflikter. Alvorlig koronavirussykdom er assosiert med hyperinflammasjon. Foto: Einar Nilsen Nylig publiserte The Lancet en artikkel av Puja Mehta og medarbeidere hvor det diskuteres om sekundaer hemofagocytisk lymfohistiocytose (HLH) kan vaere assosiert med alvorlig koronavirussykdom (covid-19) (1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 5 publications
1
18
0
1
Order By: Relevance
“…The study showed that patients with low HDL-C level had higher proportion of severe events, while further regression analysis also revealed that low HDL-C was an independent risk factor for severe events in COVID-19. Hence, HDL-C may serve in a protective role in COVID-19, Excessive inflammation is one of the important features of COVID-19 patients, especially in patients with severe cases or in those who have died [31][32][33][34]. It is often manifested by a marked increase in inflammatory factors, such as CRP and interleukins [3,35].…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that patients with low HDL-C level had higher proportion of severe events, while further regression analysis also revealed that low HDL-C was an independent risk factor for severe events in COVID-19. Hence, HDL-C may serve in a protective role in COVID-19, Excessive inflammation is one of the important features of COVID-19 patients, especially in patients with severe cases or in those who have died [31][32][33][34]. It is often manifested by a marked increase in inflammatory factors, such as CRP and interleukins [3,35].…”
Section: Discussionmentioning
confidence: 99%
“…Further release of IL 6 causes vascular leakage, activation of complement and coagulation cascade, disseminated intravascular coagulation and end organ damage. 17 , 18…”
Section: Immune Mediated Injurymentioning
confidence: 99%
“…One of the most widely accepted neuropathological mechanisms of SARS-CoV-2 is hyper-inflammatory state ( Yavarpour-Bali and Ghasemi-Kasman, 2020 ). Accordingly, the immune-mediated damage is resulted from cytokine storms, as well as the activation of T lymphocytes, endothelial cells, and macrophages which leads into vascular leakage, coagulation, and end-organ damage ( Mehta et al, 2020 ; Tveito, 2020 ). It was shown that coronavirus triggers innate immunity associated with the release of microglial-induced INF-α/β ( Savarin et al, 2018 ).…”
Section: The Pathophysiological Mechanistic Pathways Of Coronavirusesmentioning
confidence: 99%